Pengembangan Soal pada Kitab Balaghah Ma'ani Berbasis Pendekatan Open Ended malalui Media Quiz Whizzer di Pondok Pesantren - Nata, Dimas Surya; Huda, Hisbullah (Study Program of Arabic Language Teaching, 2025)
This study aims to develop questions from the Balaghah Ma’ani book using the Open-Ended approach with Quiz Whizzer media and to test their effectiveness in improving students’ creative thinking skills. The research method uses Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research subjects were 35 students in class IX at the Nurussalam Sidogede Modern Islamic Boarding School in Palembang. The research instruments included expert validation sheets, student response questionnaires, and pre- and posttests. Data were analyzed using descriptive and inferential statistics through the Shapiro-Wilk normality test, Levene’s homogeneity test, and the Paired Sample t-test. The results showed that the questions developed were valid and suitable for use, as validated by material and media experts. Statistical testing showed a significant increase in students’ scores after using Quiz Whizzer media, with an average pretest score of 52.14 and a posttest score of 87.43. The paired t-test yielded a p-value of 0.000 (p 0.05), indicating a significant difference in learning outcomes before and after media use. Therefore, open-ended questions using the Quiz Whizzer media have been proven effective in improving students’ creative thinking skills in learning Islamic sciences.